STUDENTS' PERCEPTION TOWARD READING COMPREHENSION SKILLS USING DISCUSSION TECHNIQUE THROUGH WHATSAPP - Herlina Rahayu; Efransyah Efransyah (IKIP Siliwangi, 2022)
Reading has developed into a critical tool for education, particularly in the teaching and learning processes, and it is now considered as a standard practice. Reading comprehension is the process of constructing the meaning of reading by integrating essential facts that are important in the educational process and students' achievement in school. The purpose of this study is to gain an understanding of students' perceptions of teaching reading comprehension skills through the use of a conversation strategy provided via WhatsApp. The participants in this study are 35 students in the ninth grade at SMP Unggulan Al - Amin Cimahi. Depending on the results of the student questionnaire, the researcher concludes that students' reactions to the implementation of teaching reading comprehension of narrative texts using WhatsApp data are favorable, with a total of 78 percent of positive responses and 22 percent of negative responses to the questionnaire. Keywords: Reading Comprehension, WhatsApp